Analisis Pengaruh Bantuan Pangan Non Tunai dan Program Keluarga Harapan Terhadap Kemiskinan di Kota Mojokerto Tahun 2019-2021 - Ferdiyansah, Jeffry; Kriswibowo, Arimurti (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2023)
Poverty is a condition when a person or a group has no choice to fulfill their essential privileges to maintain and maintain a noble life. The poverty rate in Mojokerto City has increased significantly over the last three years. Compared to the surrounding districts/cities, the increase in poverty is not as severe as in Mojokerto City. This study aims to analyze how PKH and BPNT influence poverty in Mojokerto City in 2019-2021. The type of data used in this research is secondary data, then for the approach that is quantitative, with the type of research descriptive analysis, using multiple linear regression through data processing in SPSS 22. The study found that PKH had a negative and significant impact on poverty, while BPNT had a positive and significant impact on poverty.